Perancangan Sistem Informasi Pembayaran Sumbangan Komite di SMKN 1 Ampek Angkek - Asra, Feby Mutiara; Okra, Riri; Supriadi, Supriadi; Musril, Hari Antoni (Institut Teknologi Pendidikan Indonesia, 2022)
This research was motivated by the discovery of problems in recording the payment of committee contributions at SMKN 1 Ampek Angkek, the recording of committee contributions payments was still conventional, where staff still had to record on the committee's contribution payment card then the payment data was recapitulated. School staff experienced difficulties in collecting financial data, paper stacking, data sharing limitations, data discrepancies and reporting delays. The research method used is the Research and Development (R&D) research method, which is a method used to produce a system, with the system development model using the System Development Life Cycle (SDLC) by applying the waterfall model consisting of Communication, Planning, Modeling, Construction , and Deployments. This committee donation payment information system uses Codeigniter 3 and PHP, the software used to design the school committee donation payment information system is sublime text, then in processing the database using MySQL. Based on the results of the research that the researchers did, the researchers succeeded in making a committee product payment information system at SMKN 1 Ampek Angkek. The results of the validity test conducted by computer experts showed this product was very valid with a value of 0.91. The results of the practicality test conducted by the administrative staff at SMKN 1 Ampek Angkek showed that this product was stated to be very practical with a score of 87%. And the results of the effectiveness test conducted with administrative staff at SMKN 1 Ampek Angkek showed this product was very effective with a value of 0.93.